Profile of Fatal Poisoning Cases in Chitradurga District, Karnataka (Indian Internet Journal of Forensic Medicine and Toxicology, 2014)
A one-year retrospective study was undertaken to ascertain the incidence of poisoning deaths in and around Chitradurga district of Karnataka state, which were autopsied at District Government Hospital, Chitradurga. Out of 343 autopsies conducted, 73 were deaths due to poisoning. The commonest age group of affected victims was 21–30 years. Males outnumbered females in a ratio of 1.8:1. The most commonly used poison was an organo-phosphorus compound. Most of the cases were suicidal in nature and maximum were from rural population.
Keywords: Poisoning; Insecticides; Insecticides Chitradurga